De l’«Spill de la vida religiosa» al «Desitjós». Notes a una novel·la al·legòrica del segle XVI - Valsalobre, Pep (Caplletra. Revista Internacional de Filologia, 2001)
The contribution of the author of this article to the study of this religious novel inspired by Ramón Llull is to demonstrate that the text we now know derives from a longer text, the author of which must have belonged to the Observants belonging to the Fransciscan order. The author also offers his reflections on diverse themes that have not been analysed so far in the abbreviated version of the «Spill de la vida religiosa».